1974
DOI: 10.1111/j.1469-8749.1974.tb03458.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Apnoea and Stridor in Spina Bifida to Other Unexplained Infant Deaths

Abstract: SUMMARY A study of infants suffering episodes of apnoea, stridor or bradycardia in association with spina bifida cystica suggests that neither anatomical nor hydrodynamic abnormalities fully explain these complications. The episodes were often heralded by a rise in the capillary pCO2, an increase in the amount of periodic breathing during sleep, and a possible increase in the proportion of rapid‐eye‐movement sleep. Episodes of life‐threatening apnoea, stridor or bradycardia were most frequent and severe at 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 12 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…A lack of timely diagnosis and management can lead to untreated SDB, with a risk for significant morbidity and mortality. Children with CM1 are at an increased risk for neurocognitive complications, including reduced intellectual quotient scores and behavioural difficulties, and may also rarely be at increased risk for adverse cardiorespiratory outcomes and death (31)(32)(33). Clinical sleep history and physical examination are not sufficiently sensitive or specific to establish a diagnosis of sleep apnea in patients with CM1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of timely diagnosis and management can lead to untreated SDB, with a risk for significant morbidity and mortality. Children with CM1 are at an increased risk for neurocognitive complications, including reduced intellectual quotient scores and behavioural difficulties, and may also rarely be at increased risk for adverse cardiorespiratory outcomes and death (31)(32)(33). Clinical sleep history and physical examination are not sufficiently sensitive or specific to establish a diagnosis of sleep apnea in patients with CM1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Complete recovery has been observed in some infants treated only with vigorous supportive care, including intubation, tracheostomy, gastrostomy, supplemental oxygen and cardiorespiratory monitoring (Wealthall et al 1974). A better understanding of the natural history of ventilatory dysfunction should lead to a more rational approach to treatment (Park et al 1983, Charney et al 1987.…”
Section: Central Ventilatory Dysfunction (Cvd)mentioning
confidence: 99%
“…While some studies observed clinical symptoms or MRI findings that may have been associated with SDB in that specific cohort of patients, 31 , 34 , 38 others did not observe any correlations between clinical symptoms or MRI findings and likelihood of developing SDB or SDB severity. 47 …”
Section: Sleep-disordered Breathing In the Child With Spina Bifidamentioning
confidence: 99%